Hildegarde von Bingen et Lorraine Vaillancourt : deux femmes rebelles dans leur siècle... - Peillon, Catherine (La pensée de midi, 2009)

Des pratiques d’artistes et de chercheuses en écologie sonore - Piché, Claire (Recherches féministes, 2009)
This article is an incursion into the domain of sound ecology based on interdisciplinary research about artists and researchers. We expose the fundamental principles of sound ecology, a discipline that emerged during the seventies, and discuss the best practices of women in sound ecology, demonstrating how this constitutes a relevant research area for women’s studies. The link between feminism and sound ecology being established, we summarize three sociopolitically relevant research projects whose methods resemble feminist action research. We conclude by reflecting on the best means to foster interdisciplinary collaboration.

Hip-hop autochtone au Québec. Oralités contemporaines au gré des ondes politiques et médiatiques - Audet, Véronique (Inter : art actuel, 2009)
An article from Inter, on Érudit.

Chansons de travail, chansons de chômage : une lecture du monde ouvrier pendant la crise à travers l’œuvre de La Bolduc - Charest, Marie-Josée (Études littéraires, 2009)
In the 1930s, Mary Travers wrote folk songs dealing with the thorny issue of the working poor during hard times. A self-styled “woman at the service of the community”, she focused on those who lost their jobs as a result of the economic crisis. Heeding tradition, she lauded the work of famers whom she perceived as the mythical representatives of an idealised “old era”. How did she reconcile her songs praising tradition with an increasingly industrial labour market ? How did she react to women entering the workforce ? What did she think of government actions in the face of dwindling employment and pressing poverty ? Did she consider herself to be a career woman, what with hers being the first successful recordings of Quebec folk songs ? Confronting or buttressing established taboos such as those about women in the workforce, she wrote songs reflecting those societal issues prevalent at the time. Yet, she set herself apart both through her trade as a songwriter and her depiction of it. The economic situation in the province of Quebec influenced how labour was perceived, and her writings, favouring the standpoint of a working woman from the lower classes where employment is a matter of both survival and pride, echoed this perception with originality. A sociological and critical analysis of her songs illustrates the societal discourse on labour that prevailed during hard times.

Micheline Coulombe Saint-Marcoux et Marcelle Deschênes : pionnières dans le sentier de la création électroacoustique - Lefebvre, Marie-Thérèse (Circuit : musiques contemporaines, 2009)
A review of “masculine” and “feminine” attitudes towards music composition of the past fifty years highlights the contributions of Micheline Coulombe Saint-Marcoux and Marcelle Deschênes to the development of Québécois electroacoustic music. The author re-creates the historical context for the composers’ childhoods, adolescences, and periods of training in Montreal and Paris, and follows this with a discussion of how they negotiated the dominant trends of the 1970s. She then turns to the composers’ roles as pioneers: in their wish to depart from well-trodden paths, Coulombe Saint-Marcoux and Deschênes turned to new technological tools that would allow them to express a new artistic sensibility. From this perspective, they should be considered the “sherpas” of Québécois electroacoustic music.

La composition musicale et la marque du genre : l’examen conscient de l’« écriture féminine » - Stévance, Sophie (Circuit, 2009)
Si les spéculations idéologiques concernant les différences biologiques entre les sexes persistent dans le domaine de la création, elles ont été mises en valeur dès 1970 par des écrivaines et plasticiennes pour oeuvrer en fonction de mythes spécifiques touchant à leur féminité, au corps de la femme chargé de stigmates, afin qu’émerge un « art féminin ». D’une certaine manière, des compositrices vont emprunter cette voie en affirmant entretenir un rapport différent de celui des hommes à l’écriture musicale. Selon elles, leur sensibilité spécifique et leur situation d’être au monde les poussent à travailler autrement, à partir de thématiques « existentielles » inspirées de leur condition sociale et culturelle. De telles circonstances ont provoqué cette quête identitaire par l’invention d’un style artistique particulier qui, paradoxalement, use de ce qui était considéré par un féminisme radical comme les pièges de la féminité. Cet article tente de montrer que ces spécificités, du moins ces constantes relevées par les créatrices expliquant leur démarche, sont le résultat de recherches esthétiques pour caractériser une création universelle au féminin, et non le produit de diktats biologiques.

Introduction : Compositrices sur la scène contemporaine - Goldman, Jonathan (Circuit: Musiques contemporaines, 2009)

De la musique de geste à la musique du son, de SuperMémé à I8U - Prévost, Hélène (Circuit, 2009)
La musique actuelle née au tournant des années 1970-1980 a connu ses heures de gloire pendant de nombreuses années. Trois femmes font partie de la lancée et demeurent à ce jour des musiciennes actives et des administratrices hors pair. Mais d’autres, artistes sonores plutôt qu’instrumentistes, émergent, au moment du tournant technologique et plus particulièrement au milieu des années 1990. Un nombre important de ces femmes développent des pratiques non instrumentales d’art audio, de musique bruitiste, de musiques mixtes, électroniques expérimentales, d’installation et de multimédia. Elles sont mal connues, méconnues des grands médias et de la plupart des lieux d’enseignement de la musique, bien que plusieurs d’entre elles les aient fréquentés. Ce moment de rencontre avec certaines d’entre elles souhaite les faire apparaître, en plein jour.